Isolation of a New Steroidal Glycoalkaloid from Solanum xanthocarpum - Parveen Fazil,; Rahat Azhar Ali, (Journal of Basic & Applied Sciences, 2021)
A new steroidal glycoalkaloid was isolated from barries of Solanum xanthocarpum, together with two other known steroidal glycoalkaloids. The structure of new steroidal glycoalkaloid was elucidated as O-(3){ α-L- rhamnopyranosyl-(1→2gal)- β-D- galactopyranosyl}-solasodine on the basis of spectroscopic analysis as well as comparison with reported spectroscopic data of related compounds.